Caracterização funcional de dois cDNAs homólogos à ciclofilina e à proteína reprimida por auxina (ARP) identificados em bibliotecas subtrativas a para floração em tomateiro - Estevam, Renata Kaline Souza (2011)
Flowering is a fundamental process in the life cycle for plant. This process is marked by vegetative to reproductive apical meristem conversion, due to interactions between several factors, both internal and external to plant. Therefore, eight subtractive libraries were constructed using apical meristem induced or not induced for two contrasting species: Solanum lycopersicum cv. Micro-Tom and Solanum pimpinellifolium. Several cDNAs were identified and among these, were selected two cDNAs: one homologous cDNA to cyclophilin (LeCYP1) and the other to Auxin repressed protein (ARP). It has observed that LeCYP1 and ARP genes are important in the developmental process to plants. In silico analysis, were used several databases with the exclusion criterion E-value <1.0x10-15. As a result, conservation was observed for proteins analyzed by means of multiple alignments and the presence of functional domains. Then, overexpression cassettes were constructed for the ARP cDNA in sense and antisense orientations. For this step, it was used the CaMV35S promoter. The cDNA orientation (sense or antisense) in relation to the promoter was determined by restriction enzymes and sequencing. Then, this cassette was transferred to binary vector pZP211 and these cassettes were transferred into Agrobacterium tumefaciens LBA4404. S. lycopersicum cv. Micro-Tom (MT) and MT-Rg1 plants were transformed. In addition, seedlings were subjected to hormone treatments using a synthetic auxin (- naphthalene acetic acid) and cyclosporin A (cyclophilin inhibitor) treatments and it was found that the hormone treatment there were changes in development of lateral roots pattern, probably related to decreases in auxin signaling caused by reduction of LeCYP1 in MT-dgt plants while cyclosporin A treatments, there was a slight delay in flowering in cv. MT plants. Furthermore, assay with real-time PCR (RT-qPCR) were done for expression level analysis from LeCYP1 and ARP in order to functionally characterize these sequences in tomato plants.